Intraoperative positive end-expiratory pressure and postoperative pulmonary complications: a patient-level meta-analysis of three randomised clinical trials. (June 2022) - Campos, Niklas S.; Bluth, Thomas; Hemmes, Sabrine N.T.; Librero, Julian; Pozo, Natividad; Ferrando, Carlos; Ball, Lorenzo; Mazzinari, Guido; Pelosi, Paolo; Gama de Abreu, Marcelo; Schultz, Marcus J.; Serpa Neto, A.; et al.
Abstract: Background: High intraoperative PEEP with recruitment manoeuvres may improve perioperative outcomes. We re-examined this question by conducting a patient-level meta-analysis of three clinical trials in adult patients at increased risk for postoperative pulmonary complications who underwent non-cardiothoracic and non-neurological surgery. Methods: The three trials enrolled patients at 128 hospitals in 24 countries from February 2011 to February 2018. All patients received volume-controlled ventilation with low tidal volume. Analyses were performed using one-stage, two-level, mixed modelling (site as a random effect; trial as a fixed effect). The primary outcome was a composite of postoperative pulmonary complications within the first week, analysed using mixed-effect logistic regression. Pre-specified subgroup analyses of nine patient characteristics and seven procedure and care-delivery characteristics were also performed. Results: Complete datasets were available for 1913 participants ventilated with high PEEP and recruitment manoeuvres, compared with 1924 participants who received low PEEP. The primary outcome occurred in 562/1913 (29.4%) participants randomised to high PEEP, compared with 620/1924 (32.2%) participants randomised to low PEEP (unadjusted odds ratio [OR]=0.87; 95% confidence interval [95% CI], 0.75–1.01; P =0.06). Higher PEEP resulted in 87/1913 (4.5%) participants requiring interventions for desaturation, compared with 216/1924 (11.2%) participants randomised to low PEEP (OR=0.34; 95% CI, 0.26–0.45). Intraoperative hypotension was associated more frequently (784/1913 [41.0%]) with high PEEP, compared with low PEEP (579/1924 [30.1%]; OR=1.87; 95% CI, 1.60–2.17). Conclusions: High PEEP combined with recruitment manoeuvres during low tidal volume ventilation in patients undergoing major surgery did not reduce postoperative pulmonary complications. Clinical trial registration: NCT03937375 (Clinicaltrials.gov ).